Clinical outcomes and cumulative healthcare costs of TAVR vs. SAVR in Asia - Tan, Elise Chia-Hui; Lee, Yung-Tsai; Kuo, Yu Chen; Tsao, Tien-Ping; Lee, Kuo-Chen; Hsiung, Ming-Chon; Wei, Jeng; Lin, Kuan-Chia; Yin, Wei-Hsian (Frontiers in Cardiovascular Medicine, 2022)
OBJECTIVES This study compared transcatheter aortic valve replacement (TAVR) and surgical aortic valve replacement (SAVR) in terms of short- and long-term effectiveness. METHODS This retrospective cohort study based on nationwide National Health Insurance claims data and Cause of Death data focused on adult patients (n=3,643) who received SAVR (79%) or TAVR (21%) between 2015 and 2019. Propensity score overlap weighting was applied to account for selection bias. Primary outcomes included all-cause mortality (ACM), hospitalization for heart failure, and a composite endpoint of major adverse cardiac events (MACE). Secondary outcomes included medical utilization, hospital stay, and total medical costs at index admission for the procedure and in various post-procedure periods. The Cox proportional-hazard model with competing risk was used to investigate survival and incidental health outcomes. Generalized estimation equation (GEE) models were used to estimate differences in the utilization of medical resources and overall costs. RESULTS After weighting, the mean age of the patients was 77.98±5.86 years in the TAVR group and 77.98±2.55 years in the SAVR group. More than half of the patients were female (53.94%). The incidence of negative outcomes was lower in the TAVR group than in the SAVR group, including 1-year ACM (11.39% vs 17.98%) and 3-year ACM (15.77% vs 23.85%). The risk of ACM was lower in the TAVR group (HR [95% CI]: 0.61 [0.44-0.84]; P=0.002) as was the risk of CV death (HR [95% CI]: 0.47 [0.30-0.74]; P=0.001) or MACE (HR [95% CI]: 0.66 [0.46-0.96]; P=0.0274). Total medical costs were significantly higher in the TAVR group than in the SAVR in the first year after the procedure ($1,271.89±4,048.36 versus $887.20±978.51; P=0.0266); however, costs were similar in the second and third years after the procedure. The cumulative total medical costs after the procedure were significantly higher in the TAVR group than in the SAVR group (adjusted difference: $420.49±176.48; P=0.0172). CONCLUSIONS In this real-world cohort of patients with aortic stenosis, TAVR proved superior to SAVR in terms of clinical outcomes and survival with comparable medical utilization after the procedure.